2007
DOI: 10.1038/sj.npp.1301387
|View full text |Cite
|
Sign up to set email alerts
|

Increased Anterior Cingulate/Medial Prefrontal Cortical Glutamate and Creatine in Bipolar Depression

Abstract: Proton magnetic resonance spectroscopy ( 1 HMRS) is an in vivo brain imaging method that can be used to investigate psychotropic drug mechanism of action. This study evaluated baseline 1 HMRS spectra of bipolar depressed patients and whether the level of cerebral metabolites changed after an open trial of lamotrigine, an anti-glutamatergic mood stabilizer. Twenty-three bipolar depressed and 12 control subjects underwent a MRS scan of the anterior cingulate/medial prefrontal cortex. The scan was performed on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
4
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(142 citation statements)
references
References 81 publications
5
127
4
4
Order By: Relevance
“…50,51 Our results are also in general agreement with a recent report of increased levels of glutamate in post-mortem frontal cortex samples from patients with bipolar disorder 27 and an 1 H-MRS investigation at 1.5 T that previously reported increased anterior cingulate cortical glutamate in bipolar depression. 52 However, information on antidepressant intake in the latter study is lacking while a subset of patients are reported to have received lithium.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 Our results are also in general agreement with a recent report of increased levels of glutamate in post-mortem frontal cortex samples from patients with bipolar disorder 27 and an 1 H-MRS investigation at 1.5 T that previously reported increased anterior cingulate cortical glutamate in bipolar depression. 52 However, information on antidepressant intake in the latter study is lacking while a subset of patients are reported to have received lithium.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, we report metabolite levels in AU. We avoided internal referencing to creatine because of recent reports suggesting creatine abnormalities in BD (Frye et al, 2007;Ö ngür et al, 2009a) and internal referencing to water was not possible, lacking usable water unsuppressed spectra in this study. Our approach does not correct for inter-subject sources of variance, but the longitudinal within-subject design of our study and statistical analysis mitigates the problems of variability inherent to many cross-sectional MRS studies.…”
Section: Limitationsmentioning
confidence: 99%
“…Increased Glx levels have been shown in the depressed (Bhagwagar et al, 2007;Frye et al, 2007), manic (Cecil et al, 2002;Michael et al, 2003), and euthymic (Dager et al, 2004) phases of BD, as well as in rapid-cycling BD (Michael et al, 2009). However, the physiological significance of Glx is unclearFunderscoring the need for separate glutamate and glutamine measures.…”
Section: Introductionmentioning
confidence: 99%
“…We used absolute metabolite levels instead of ratios with creatine to avoid a bias through systematic drifts in the magnitude of the creatine resonance, as suggested by previous studies. 18,[21][22][23][24] VOI tissue segmentation and total hippocampal volume To control for the effect of potential structural differences in the region studied, we assessed tissue composition within the VOIs and total hippocampal volume as follows. The amount of each tissue -grey matter, white matter and CSF -was quantified for each VOI, so the scans were first separated in the 3 different tissues using SPM8 software (Wellcome Trust Centre for Neuroimaging, www.fil.ion.ucl.ac.uk/spm) running under MATLAB 7.8.0 (MathWorks).…”
Section: Mrs Scanning Proceduresmentioning
confidence: 99%